Stromal Cells Underlining the Paths From Autoimmunity, Inflammation to Cancer With Roles Beyond Structural and Nutritional Support - Honan, Amanda M.; Chen, Zhibin (Frontiers in Cell and Developmental Biology, 2021)
Stromal cells provide structural support and nutrients in secondary lymphoid organs and non-lymphoid tissues. However, accumulating evidence suggests that a complex relationship exists between stromal cells and immune cells. Interactions between immune cells and stromal cells have been shown to influence the pathology of both autoimmunity and cancer. This review examines the heterogeneity of stromal cells within the lymph node and non-lymphoid tissues during both homeostatic and inflammatory conditions, in particular autoimmunity and cancer, with the goal of better understanding the complex and apparently paradoxical relationship between these two classes of diseases. The review surveys potential novel mechanisms involving the interactions between stromal cells and immune cells which may contribute to the development, pathology and underlying connection between autoimmunity and cancer, including potential pathways from autoimmune inflammation to either “hot” or “cold” tumors. These interactions may provide some insights to explain the rising incidence of both autoimmunity and cancer in young women in industrialized countries and have the potential to be exploited in the development of new interventions for preventions and treatments of both autoimmune diseases and cancer.